Conflict Management of Madrasah Heads in Improving Teacher Performance in Madrasah Ibtidaiyah Al Izudiniyah Cipulus Wanayasa Purwakarta Regency - Sanusi, Uu; Haryono, Pauzan (Proceeding International Conference on Education, 2023)
Conflict management in the leadership of the principal aims to provide solutions to problems that arise in improving teacher performance. Good conflict management has a positive effect on community life, organization, and work atmosphere. This research is intended to describe existing phenomena, both natural phenomena and man-made phenomena. These can be forms, activities, characteristics, changes, relationships of similarities and differences between one phenomenon and another.This qualitative research uses a descriptive method, where research describes symptoms, events, events that occur now and focuses on actual problems as during the research. The results of this study include;  1) The role and function of the Head of Madrasah in improving teacher performance, among others; a) Involve teachers in upgrading, b) mobilize teachers to evaluate learning outcomes, c) Use learning time effectively. 2) Fator inhibitors include; a) Madrasah educators do not have much time to carry out coaching, b) Diversity of HR vision. Differences in perception often arise when competency coaching of educators (teachers) will be held.